Incidence and Predictive Factors of Tibial Fracture with Occult Posterior Ankle Fractures. (8th December 2021) - Wang, Dafeng; Yang, Jie; Dong, Xiaomin; Zhou, Shengtuo; Wang, Chaonan
Abstract : Background. Few studies exist on the predictive factors of tibial fractures with hidden posterior ankle fractures. Objective . To study the incidence and predictive factors of tibial fractures with occult posterior ankle fractures. Methods . Tibial fracture patients were prospectively selected who were admitted to our hospital from January 2016 to May 2021 and their general clinical data, X-ray images, CT images, and other imaging data were collected and then divided them into posterior malleolus fracture group and nonposterior malleolus fracture group according to the presence or absence of posterior malleolus fractures. Multivariate regression analysis and receiver operating curves (ROC) were performed to analyze the influencing factors of tibial fracture with occult posterior ankle fracture. Results . CT showed that 25 (13.44%) patients had occult posterior ankle fractures among 186 patients with tibial fracture. There was no significant difference in gender, age, and locations of tibial fracture between the two groups (P > 0.05 ). There were statistical differences in the types, locations, and lengths of patients with tibial fracture but without posterior malleolus fractures. The length of the tibia fracture group was significantly lower than the tibia with posterior ankle fracture group (P < 0.05 ). Logistics regression analysis showed that tibial fracture with occult posterior ankle fracture was not significantly correlated with gender, age, and location of tibial fracture (P > 0.05 ), but was significantly correlated with tibial fracture type, location, and length (HR = 1.830, P = 0.035 ; HR = 5.161, P = 0.004 ; HR = 1.126, P = 0.030 ). The ROC curve showed that the AUC of length of tibial fracture with occult posterior ankle fracture was 0.599. The YD index suggested that the best cut point for the prediction of tibial fracture with occult posterior ankle fracture was above 13.18%. The sensitivity and specificity of spiral tibial fracture and distal 1/3 tibial fracture for prediction were 88.00% and 63.35%, 92.00%, and 58.39%, respectively, which was significantly higher than that of tibial fracture length (P < 0.05 ). Conclusion. Patients with tibial fractures have a higher incidence of occult posterior ankle fractures. Spiral tibial fractures and distal 1/3 tibial fractures have a higher predictive value for tibial fracture with occult posterior ankle fractures and can help clinical detection as soon as possible, which is a more accurate and appropriate treatment.